The Role of Mosques and Religious Schools in Pakistan's Fundamentalism - Aliakbar Amini; Seyed Asadolah Athari; Alireza Noura (هنر اسلامی, 2020)
Abstract Abul A’la Maududi (1903-1979) is one of the leading thinkers and philosophers of the Indian subcontinent whose ideas have had an immediate impact on Islamic fundamentalism in Pakistan. Maududi believed in the Ideological-Islamic realization, and in his thoughts concepts such as "God's sovereignty", "Islamic political system", "Confrontation with the West", "Necessity of the realization of the original Islamic society", "Islamic education", "Jihad" and other concepts with a distinctive Islamic essence were of importance. With the formation of Pakistan in 1947 and the feedback of Maududi s philosophies, this country has until today been renowned as a cradle for Islamic fundamentalism. Islamic fundamentalism considered as an ideology has certain philosophical-political components, propositions, and foundations that distinguish it from other ideologies of the 20th century such as liberalism, socialism and nationalism among others. Islamic fundamentalism, despite its diversity in opinion and practice in the Islamic world, has common intellectual and political foundations, including: the comprehensiveness and inclusiveness of the Islamic religion, the link between religion and politics, the necessity to return to the principles and foundations of Islam, the establishment of Islamic rule, pragmatism, and devising a practical plan and strategy for the transition from the non-Islamic conditions to the ideal Islamic situation. This article is a descriptive-analytic research study in which resources are gathered based on a library method. The results of this study indicate that Maududi’s notions have led to the growth of Islamic fundamentalism and have influenced various Islamic fundamentalist groups in Pakistan. Such influence can be traced to the process of Islamic identification of Pakistan's political system, the growth and expansion of Islamic parties, religious schools, and fundamentalist organizations and groups in the country. Research aims: 1. Identifying the ideological orientation of Islamic fundamentalist ideology in the Pakistani political system. 2. Explain the continuing role of mosques and religious schools in shaping Pakistan's fundamentalism. Research questions: 1. What effect did Maududi’s ideas have on the Islamic fundamentalism in Pakistan? 2. How can the role of mosques and religious schools be explained in the fundamentalism of the Pakistani people?